2010
DOI: 10.1111/j.1365-2435.2010.01769.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in fine root productivity between mixed‐ and single‐species stands

Abstract: Summary1. The diversity-productivity debate has so far been focused above-ground, despite that belowground production can account for approximately half of total annual net primary production, mostly from fine roots. 2. Here, we investigate the fine root productivity of mature, fire-origin stands of Populus tremuloides -Picea spp. -Abies balsamea (mixed-species stands) and relatively pure P. tremuloides (single-species stands) in two regions of North American boreal forest to better understand the link between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 43 publications
3
119
3
3
Order By: Relevance
“…However, few studies have examined belowground productivity in mixtures and even fewer have compared above-and belowground productivity (Forrester et al, 2006;Epron et al, 2013). Belowground overyielding has not been demonstrated to occur in mature temperate forests (Meinen et al, 2009a(Meinen et al, , 2009bJacob et al, 2013) although root differentiation led to higher fine root productivity in young stands (Lei et al 2012) whereas in boreal forests fine root overyielding was observed in mature stands originated after fire (Brassard et al, 2011). Interspecific competition can also have a strong impact on crown structure (Bayer et al, 2013) and crown allometry .…”
Section: Species Interaction and Species Richness -Ecosystem Functioningmentioning
confidence: 99%
“…However, few studies have examined belowground productivity in mixtures and even fewer have compared above-and belowground productivity (Forrester et al, 2006;Epron et al, 2013). Belowground overyielding has not been demonstrated to occur in mature temperate forests (Meinen et al, 2009a(Meinen et al, , 2009bJacob et al, 2013) although root differentiation led to higher fine root productivity in young stands (Lei et al 2012) whereas in boreal forests fine root overyielding was observed in mature stands originated after fire (Brassard et al, 2011). Interspecific competition can also have a strong impact on crown structure (Bayer et al, 2013) and crown allometry .…”
Section: Species Interaction and Species Richness -Ecosystem Functioningmentioning
confidence: 99%
“…Conventionally, when ingrowth cores with short incubation times (1 or < 2 yr. ) are used, FRP is estimated as the mass of the fine roots extracted from the ingrowth core (Idol et al 2000;Valverde-Barrantes et al 2007;Aragão et al 2009;Brassard et al 2011;Laiho et al 2014). But using such short incubation times (< 2 yr) may result in underestimation (Steele et al 1997;Vogt et al 1998;Finér and Laine 2000).…”
Section: Calculation Of Fine-root Productionmentioning
confidence: 99%
“…[ 16,[80][81][82][83][84][85] Nutrient mineralization P F Changes in nitrogen mineralization and nitrification rates can influence nitrogen availability. Lack of mycorrhizal colonization of tree roots in non-native species may be overcome through admixture of native species and increase uptake.…”
Section: Introductionmentioning
confidence: 99%